Economic Prospects of Balanced Development of International Relations - Viktorovna Tretyakova, Galina; Andranikovna Azarova, Ofeliia; Victorovna Levchenko, Victoria; Vladimirovna Meshcheryakova, Olga; Yevgenievna Lebedeva, Olga (International Journal of Engineering and Technology, 2018)
The article deals with the systematization of economic prospects of balanced development of international relations. It is established that the prerequisites for rapid development are special conditions of certain factors, which acquire different acuteness or form as institutional determinants of development. It is proved that the balanced development of international relations is associated not only with economic issues, but also with social features, political conflicts, and history. Globalization, which has originally manifested itself as liberalization, and then as the integration of capital, goods, and labor into a single world market also complicates the problem. The article highlights the importance of specialization because it is specialization that provides an opportunity to increase efficiency at the level of individuals, organizations, regions, and countries through the effect of scale, comparative advantages, and technological changes.Â Â